Hubungan Antara Paritas Dan Umur Ibu Dengan Kejadian Plasenta Previa - Indriyani Maya Lestari; Nurul Misbah (Jurnal Obstretika Scientia, 2014)
This study aimed to determine the relationship between parity and maternal age with the incidence of placenta previa in hospitals Dr. Adjidarmo Gecko 2011. Type retrospective case-control study approach. From the results of this study there was a significant relationship between parity and incidence of placenta previa (P value = 0.002) and there is a significant relationship between maternal age with the incidence of placenta previa (P value = 0.000). Expected health workers provide health education regarding the PUP as seen from the high incidence of placenta previa at age 20 years and 35 years. Because of the PUP, both women and men prepared from all aspects: health, economics, psychology and religion. So that the EFA can be prepared to wade through family life. And promoting the health workers more about the family planning program as seen from the high incidence of placenta previa in women with parity multiparous and grandemultipara. Increase awareness of the danger signs of pregnancy.